The application of graphitic carbon nitride for the adsorption of Pb2+ ion from aqueous solution. (14th July 2017) - Zhu, Lin; You, Liangjun; Wang, Ya; Shi, Zhaoxin
Abstract: This study appraised the potential application of graphitic carbon nitride (g-C3 N4 ) as an adsorbent for removal of Pb 2+ ion from aqueous solution. The g-C3 N4 was prepared by direct calcination of the low-cost melamine, and its morphology and microstructure were analyzed. Moreover, the effects of initial solution pH, initial Pb 2+ ion concentration, adsorption time, and adsorbent dosage on the adsorption properties of the g-C3 N4 were investigated. Two widely used isotherm models were used to describe the experimental equilibrium data, and the Freundlich isotherm model described well. Two widely used kinetic models were used to the fit of the adsorption experimental data, and the pseudo-second-order kinetic model fitted well. The maximum adsorption percentage and maximum adsorption capacity were 98.5% and 7.4 mg g −1, respectively. In addition, the recycling of g-C3 N4 for the removal of Pb 2+ was investigated, and the results indicated that g-C3 N4 owned a good reusability.